Quantitative research methods in translation and interpreting studies - Mellinger, Christopher D.; Hanson, Thomas A. (Routledge, Taylor & Francis Group, 2017)
This user-friendly guide is the essential primer on quantitative methods for all students and researchers in translation and interpreting studies. Accompanying materials are available online, including step-by-step walkthroughs of how analysis was conducted, and extra sample data sets for instruction and self study.